Phosphorus Sources and Risk Potential: Organic and Inorganic Fertilizers - Vimala D. Nair; Willie G. Harris (EDIS)
One of the factors that determines whether a source of phosphorus will have a negative impact on water quality is solubility. This 3-page fact sheet discusses the significantly different solubility of commonly found phosphorus sources in Florida. Written by V.D. Nair and W.G. Harris and published by the UF Department of Soil and Water Science, October 2011. (UF/IFAS photo by Milt Putnam)